Increase In Total Dissolved Solids (TPT) and Vitamin C In Tomato using Edible Coating Aloe Vera and Vacuum Packaging - Rina Ningtyas; Septanty Mutia Dewi; Novi Purnama Sari (Indonesian Journal of Contemporary Multidisciplinary Research, 2023)
Edible coating is a technique to increase the shelf life of tomatoes. The purpose of this study was to determine the best concentration for using aloe vera as a coating material and to analyze the effect of the combined use of aloe vera edible coatings packed in vacuum on the shelf life of tomatoes. The study used an experimental method consisting of 4 levels, namely without coating (K0V), 30% aloe vera coating (K30V), 50% aloe vera coating (K50V),and 70% aloe vera coating (K70V). The results showed that the coating treatment of aloe vera had an effect on the total dissolved solids (TPT) and vitamin C in storage of tomatoes, although based on statistical results it did not show significant results. The best concentration to maintaince the shelf life of tomatos is aloe vera coating 30% (K30V) treatment was the best concentration